2012
DOI: 10.1002/ijc.27844
|View full text |Cite
|
Sign up to set email alerts
|

Mortality audit of the Finnish cervical cancer screening program

Abstract: Incidence-based evaluations of cervical cancer screening programs have suggested age-specific impacts and there is uncertainty regarding the effectiveness of screening outside the ages of 30-60 years. We audited the screening histories of cervical cancer deaths and conducted a case-control evaluation of the effectiveness of organized screening in different ages with mortality as outcome. We included all 506 cervical cancer deaths in Finland in 2000-2009 due to cancers diagnosed in 1990 or later, and 3,036 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 13 publications
3
38
0
1
Order By: Relevance
“…Vicus et al (2014) analysed 1052 deaths from cervical cancer in Canada, and found that attending screening in the 3–36 months before cervical cancer diagnosis reduced mortality by 40–72%, depending on age, but that screening 37–60 or 61–120 months before diagnosis was not associated with any reduction in risk. Lonnberg et al (2013) analysed data on 506 women who had died from cervical cancer in 2000–2009. Overall, they reported a 66% reduction in mortality associated with attending a single programme screen.…”
Section: Discussionmentioning
confidence: 99%
“…Vicus et al (2014) analysed 1052 deaths from cervical cancer in Canada, and found that attending screening in the 3–36 months before cervical cancer diagnosis reduced mortality by 40–72%, depending on age, but that screening 37–60 or 61–120 months before diagnosis was not associated with any reduction in risk. Lonnberg et al (2013) analysed data on 506 women who had died from cervical cancer in 2000–2009. Overall, they reported a 66% reduction in mortality associated with attending a single programme screen.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the cytological labs working outside the programme in the opportunistic screening are not monitored and their quality is unknown. Data on mortality audits and interval cancers have been published for some countries [45], but no such attempts have been made for Poland yet. Quality of colposcopy, and histopathology should be assured as well [46].…”
Section: Discussionmentioning
confidence: 99%
“…1 Adjusted for age, mother tongue, municipality type, education level, marital status and geographical location. 2 Including also 163 women aged 25-29 years in the routine screening group and 38 in the self-sampling group. 3 Including also 279 women aged 65-67 years in the routine screening group and 33 in the self-sampling group.…”
Section: Discussionmentioning
confidence: 99%
“…2 Option valid only in 2012 invitations. 3 Women received a letter informing them about the upcoming self-sampling test and giving an opportunity to decline beforehand.…”
Section: Effects On Screening Participationmentioning
confidence: 99%
See 1 more Smart Citation